Latent autoimmune diabetes in adults - Leslie, Richard David (Henry Stewart Talks, 2013)
Autoimmunity is induced in early life, Autoimmunity involves non-genetic effects which occur in childhood, At least 2 non-genetic effects are involved in predisposing to type 1 diabetes, The age at which autoimmune diabetes is diagnosed affects the clinical and immunogenetic pattern of the disease, Autoimmune diabetes in adults in Europe as in China is the most prevalent form of autoimmune diabetes
Archived at 2021/10/31